2015
DOI: 10.1097/inf.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Pneumococcal Nasopharyngeal Carriage of Vaccine Serotypes After the Introduction of the 13-Valent Pneumococcal Conjugate Vaccine in Children in Atlanta, Georgia

Abstract: Introduction of PCV13 for universal infant use was associated with significant reductions in nasopharyngeal carriage of PCV13 serotypes and resistant strains. Carriage of non-PCV13 serotypes increased modestly, particularly serotype 35B. Further investigation is warranted to determine whether nonvaccine pneumococcal serotypes carried in the nasopharynx are associated with significant replacement disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
91
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 19 publications
14
91
2
Order By: Relevance
“…The high sensitivity of this UAD assay allows for the possibility that it will also detect small amounts of polysaccharide antigen in urine as a result of carriage as well as disease. Pneumococcal carriage rates in children range from 30% to 86%, with higher rates in lower-income countries (65)(66)(67)(68)(69)(70)(71)(72), and studies have found positive BinaxNOW results in healthy children carrying pneumococci in their nasal pharynges (24)(25)(26)(27). Adult carriage rates are much lower than those of children; carriage in the United Kingdom is predicted to be approximately 3.4% (66).…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity of this UAD assay allows for the possibility that it will also detect small amounts of polysaccharide antigen in urine as a result of carriage as well as disease. Pneumococcal carriage rates in children range from 30% to 86%, with higher rates in lower-income countries (65)(66)(67)(68)(69)(70)(71)(72), and studies have found positive BinaxNOW results in healthy children carrying pneumococci in their nasal pharynges (24)(25)(26)(27). Adult carriage rates are much lower than those of children; carriage in the United Kingdom is predicted to be approximately 3.4% (66).…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent US study showed 15% and 14% of pneumococcal isolates from the nasopharynx of 656 children in Atlanta were 35B and 15B/C, respectively. 35 Serotypes 35B and 15B/C have also been identified as increasing causes of IPD. Adult pneumococcal surveillance data are limited, however, between 2009 and 2012, Mendes observed an increase in prevalence of pneumococcal infections in hospitalized adults in the US due to serotypes 15B/C from 2.7% to 6.3% and 35B from 3.6% to 8.2%.…”
Section: Discussionmentioning
confidence: 99%
“…40 Similarly, Desai found that 9% and 11% of IPD in studied children in Atlanta were caused by serotypes 35B and 15B/C, respectively. 35 By 2015, the CDC's Active Bacterial Core Surveillance program showed that serotypes 15B/ C and 35B have emerged as 2 of the top 4 most frequent causes of IPD in children less than 5 years of age. 41 Furthermore, as serotypes 15B/C and 35B emerged, it became clear that many isolates are b-lactam resistant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing proportions of clinical isolates within serotypes 35B and 6C in the United States with decreased susceptibility to ␤-lactams have been reported (295). Resistant serotype 35B (serotype 35B/ST558) IPD was virtually absent among children in the preconjugate vaccine era, but during the past decade, serotypes 35B, 6C, and additional serotypes have increased in both carriage (296,297) and IPD cases representing all ages (50,294,295), potentially as a consequence of the removal of competing conjugate vaccine serotypes from the pediatric carriage reservoir. The PMEN-24 serotype 35B clonal complex has emerged to become the predominant pediatric ␤-lactam-resistant IPD serotype (50).…”
Section: Current Moderately Successful Antibiotic-resistant Nonvaccinmentioning
confidence: 99%